Managing glyphosate-resistant common ragweed (Ambrosia artemisiifolia): effect of glyphosate-phenoxy tank mixes on growth, fecundity, and seed viability. Issue 1 (30th December 2016) - Bae, Jichul; Nurse, Robert E.; Simard, Marie-Josée; Page, Eric R.
Abstract : Common ragweed is one of the most important weeds in the soybean-producing areas of the United States and Canada. Recently, glyphosate-resistant (GR) biotypes have been reported in 15 states and one Canadian province. Reducing the proliferation of GR common ragweed biotypes is complicated by the high fecundity and complex seed germination behavior exhibited by this species. An experiment was conducted to evaluate the efficacy of late herbicide applications for reducing seed production, seed weight, and seed viability of a GR common ragweed biotype. Herbicide treatments included: water control, glyphosate, 2, 4-D, dicamba, 2, 4-D plus glyphosate, and dicamba plus glyphosate. Treatments were applied at the appearance of male flower buds (Biologische Bundesanstalt, Bundessortenamt and Chemical industry scale [BBCH] 51) or at the early female flowering stage (BBCH 61 to 63). At BBCH 51, 2, 4-D or dicamba applied alone or in a tank mix with glyphosate reduced seed production by an average of 80%. Conversely, seed production following these same treatments applied at BBCH 61 to 63 was not significantly different from when glyphosate was applied alone. At this stage of development, all herbicide treatments reduced seed viability relative to the control; however, treatments containing 2, 4-D or dicamba resulted in significantly lower viability than when glyphosate was applied alone. These results suggest that the application of tank mixes containing 2, 4-D or dicamba have the potential to limit seed production of GR common ragweed when applied on or before BBCH 51. The development of new technologies that facilitate the in-crop application of tank mixes containing 2, 4-D or dicamba may therefore be an effective option for limiting population establishment, seedbank replenishment, and future spread of glyphosate-resistant alleles.